2005
DOI: 10.1093/eurheartj/ehi504
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial wave reflections predict severe cardiovascular events in patients undergoing percutaneous coronary interventions

Abstract: Increased arterial wave reflections are independently associated with an increased risk for severe short- and long-term cardiovascular events in patients undergoing PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
2
36

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(200 citation statements)
references
References 26 publications
(24 reference statements)
6
153
2
36
Order By: Relevance
“…29,30 In our study, central AIx correlated with WLR. It is well known that age-related changes of central AIx are nonlinear, increasing more in younger (<50 years) individuals, suggesting that central AIx might be a more sensitive marker of arterial stiffening in the younger patients.…”
Section: Discussionsupporting
confidence: 54%
“…29,30 In our study, central AIx correlated with WLR. It is well known that age-related changes of central AIx are nonlinear, increasing more in younger (<50 years) individuals, suggesting that central AIx might be a more sensitive marker of arterial stiffening in the younger patients.…”
Section: Discussionsupporting
confidence: 54%
“…Aortic pressure augmentation due to wave reflection could cause myocardial ischemia by increasing the left ventricular wasted effort and ejection duration, even in the absence of overt coronary stenosis (Nichols et al 2013). As summarized in previous reviews (Vlachopoulos et al 2010;Hashimoto and Ito 2012), several prospective studies conducted on coronary artery disease patients have demonstrated that the central pulse pressure and augmentation index predict future cardiovascular events, and the predictive ability is superior to (or independent of) the brachial pressure (Chirinos et al 2005;Weber et al 2005Weber et al , 2010Jankowski et al 2008).…”
Section: Central Hemodynamics and Heartmentioning
confidence: 99%
“…It is considered the 'gold standard' for the assessment of aortic stiffness, 25,26 and cfPWV and AIx have the greatest amount of evidence to support their predictive value for cardiovascular events in healthy and diseased populations. 26,[28][29][30]75,79,80 Therefore, other parameters of arterial stiffness, such as local distensibility or compliance, may not be as valuable to assess the vascular effects of OSA and are not as useful clinical parameters.…”
Section: Therapeutic and Clinical Implicationsmentioning
confidence: 99%